1974
DOI: 10.1172/jci107532
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture Studies of Phosphate Transport in the Proximal Tubule of the Dog THE RELATIONSHIP TO SODIUM REABSORPTION

Abstract: A B S T R A C T Micropuncture studies were performed in the dog to examine the relationship between sodium and phosphate transport in the proximal tubule. In hydropenic, thyroparathyroidectomized animals, administration of parathyroid extract, saline, or acetazolamide resulted in a fall in proximal tubule fluid-to-plasma (TF/P) inulin ratio as well as a rise in tubule fluid-toplasma ultrafilterable (TF/UF) phosphate ratio. A correlation was found between the changes in fractional reabsorption of sodium and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

1974
1974
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 53 publications
6
34
1
Order By: Relevance
“…Lavender and Pullman have also observed increased phosphate absorption when they infused calcium into the renal artei ies of dogs (38). Wen, on the other hand, could not detect a decrease in phosphate clearance after the infusion of CaCL into dogs (39). Also at variance with our studies are the observations of Eisenberg (40) who reported increased clearance of phosphate after infusion of calcium for 72 h in hypoparathyroid patients.…”
Section: Discussioncontrasting
confidence: 69%
“…Lavender and Pullman have also observed increased phosphate absorption when they infused calcium into the renal artei ies of dogs (38). Wen, on the other hand, could not detect a decrease in phosphate clearance after the infusion of CaCL into dogs (39). Also at variance with our studies are the observations of Eisenberg (40) who reported increased clearance of phosphate after infusion of calcium for 72 h in hypoparathyroid patients.…”
Section: Discussioncontrasting
confidence: 69%
“…Volume expansion per se has subsequently been shown to reduce proximal phosphate reabsorption (8,9,31,32). Furthermore, administration of acetazolamide, which tends to lower the in situ pH in the proximal tubule (21), also results in inhibition of phosphate reabsorption (10,11,30). This latter effect has recently been attributed to stimulation of renal adenyl cyclase by acetazolamide (33), a mechanism of action thought to be similar to that of PTH (5).…”
Section: Resultsmentioning
confidence: 99%
“…Recent micropuncture studies have demonstrated several important features of the renal reabsorptive process for inorganic phosphate (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). First, the proximal tubule is responsible for most but not all of phosphate reabsorption, the most avid site being the early portion of the proximal convoluted tubule (2,4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations